Analysis of the Mediating Effect of Micro Business Growth on Productive Zakat Utilization, Information Technology, and Mustahiq’s Welfare - Simbolon, Siti Ena Aisyah; Afdawaiza (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
This study aims to analyze the impact of productive zakat and information technology on the welfare of Mustahiq through the growth of micro-businesses at BAZNAS DIY, LAZISMU DIY, and LAZISNU DIY. Quantitative analysis was employed in this study with a sample size of 39. The data analysis technique utilized was Structural Equation Modeling and Partial Least Squares (SEM-PLS), facilitated by the Smart-PLS 3.0 application. The findings of this research indicate that both productive zakat and information technology exert a significant positive influence on the growth of micro-businesses. However, productive zakat alone does not significantly affect the welfare of Mustahiq. On the other hand, micro-business growth demonstrates a significant positive effect on Mustahiq’s welfare. Furthermore, productive zakat and information technology significantly contribute to the welfare of Mustahiq through the mediation of micro-business growth. Originality/Value: This study seeks to explore the relationships between productive zakat, micro-business growth, information technology, and mustahiq welfare. Additionally, it aims to assess the impact of productive zakat provision and information technology utilization on mustahiq welfare, contributing to the discourse on effective poverty alleviation strategies in Indonesia.